Pengembangan Modul Elektronik Fisika berbasis Saintifik Menggunakan Software Sigil pada Materi Suhu, Kalor, dan Perpindahan Kalor - Rohmah, Erlina Fatkur; Budiharti, Rini; Fauzi, Ahmad (Jurnal Materi dan Pembelajaran Fisika, 2022)
This study has the following objectives: (1) Explaining the stages of the development process of electronic modules on temperature, heat, and heat transfer materials using Sigil software, (2) Explaining the final specifications of scientific-based electronic modules on temperature, heat, and heat transfer materials using Sigil software. This study uses three steps of the development method with the ADDIE model, namely (1) analysis, (2) design, and (3) development. The research instruments used in this study include a needs analysis questionnaire, a validation questionnaire for the validator, a student test sheet questionnaire, and a draft interview question. The data are qualitative data and quantitative data. The study was conducted in three high schools in Surakarta Residency, namely SMAN 1 Surakarta, SMAN 1 Kartasura, and SMAN 1 Ngemplak Boyolali. The data sources consisted of two experts, three high school physics teachers, and 90 students. The data analysis technique used is qualitative analysis and quantitative analysis. The conclusions of this development research are (1) The development step of the scientific-based physics learning electronic module using Sigil software on the material of temperature, heat, and heat transfer includes the stage, completion step, and module testing step. (2) The developed physics learning electronic module presents temperature, heat, and heat transfer material which consists of 6 sub-materials, namely temperature, heat, the effect of heat on changes in substances (solids), expansion of solids, black principle, and heat transfer. The background of the module display in each learning activity is based on a scientific flow. Based on the results of expert validation and student assessment, the developed module meets the criteria very well. This research can be used as a preliminary research and reference in developing similar products.